Energy and Economic Growth Nexus: A Long-run Relationship in Indonesia - Darrian, Kelvan; Scholastica, Patricia; Kadarusman, Yohanes B.; Rafitrandi, Dandy (Economics and Finance in Indonesia, 2023)
Energy plays an important role in economic growth in which it affects total factor productivity (TFP). Energy conservation efforts to address global climate change may adversely affect economic growth, particularly in the long run. This study analyses the short- and long-run relationship between energy consumption (both non-renewable (NREC) and renewable (REC)) and economic growth in Indonesia within the period of 1985 to 2019. Using the vector-error correction model (VECM), the paper discovered a short-run unidirectional causality from NREC and REC to economic growth. Economic growth in Indonesia is dependent on energy consumption. The finding proves the growth hypothesis in the energy and economic growth nexus (EGN). In the long run, only NREC has a unidirectional causality to economic growth, while REC is independent. REC supports the neutrality hypothesis rather than the growth hypothesis. The neutrality of REC in promoting economic growth in the long run indicates that Indonesia remains highly dependent on NREC to generate economic growth. Consequently, lowering NREC will adversely affect economic growth both in the short and long run. Nevertheless, Indonesia has signed a commitment to reduce carbon emissions vis a vis NREC in the context of climate change. The findings suggest that Indonesia should conduct energy transition toward REC, while conserving NREC in addition to accumulating physical and human capital to sustain high economic growth in the long run.